MassMin 2008 : Proceedings of the 5th International Conference and Exhibition on Mass Mining, Luleå, Sweden 9-11 June 2008 - Schunnesson, Håkan; Nordlund, Erling (Luleå tekniska universitet, Drift, underhåll och akustik, 2008)
Godkänd; 2008; 20080609 (ysko)